A longitudinal study of the infant nasopharyngeal microbiota: The effects of age, illness and antibiotic use in a cohort of South East Asian children. - Susannah J Salter; Claudia Turner; Wanitda Watthanaworawit; Marcus C de Goffau; Josef Wagner; Julian Parkhill; Stephen D Bentley; David Goldblatt; Francois Nosten; Paul Turner (Public Library of Science (PLoS), 2017)
A longitudinal study was undertaken in infants living in the Maela refugee camp on the Thailand-Myanmar border between 2007 and 2010. Nasopharyngeal swabs were collected monthly, from birth to 24 months of age, with additional swabs taken if the infant was diagnosed with pneumonia according to WHO clinical criteria. At the time of collection, swabs were cultured for Streptococcus pneumoniae and multiple serotype carriage was assessed. The bacterial 16S rRNA gene profiles of 544 swabs from 21 infants were analysed to see how the microbiota changes with age, respiratory infection, antibiotic consumption and pneumococcal acquisition. The nasopharyngeal microbiota is a somewhat homogenous community compared to that of other body sites. In this cohort it is dominated by five taxa: Moraxella, Streptococcus, Haemophilus, Corynebacterium and an uncharacterized Flavobacteriaceae taxon of 93% nucleotide similarity to Ornithobacterium. Infant age correlates with certain changes in the microbiota across the cohort: Staphylococcus and Corynebacterium are associated with the first few months of life while Moraxella and the uncharacterised Flavobacteriaceae increase in proportional abundance with age. Respiratory illness and antibiotic use often coincide with an unpredictable perturbation of the microbiota that differs from infant to infant and in different illness episodes. The previously described interaction between Dolosigranulum and Streptococcus was observed in these data. Monthly sampling demonstrates that the nasopharyngeal microbiota is in flux throughout the first two years of life, and that in this refugee camp population the pool of potential bacterial colonisers may be limited.